Poetic tradition and creative consonance (Eurasian Journal of Philology Science and Education, 2023)
The article provides a poetic analysis of the poems of Abai Kunanbaevich and Magjan Jumabaev and Mukagali Makatayev. Describing the manifestation of the tradition of Abai in the poetry of Mukagali, the characteristics of its features and methods of artistic design in the lyrical poems of poets are given. The nature of the use of means of artistic expression in the works of the double poet, the expressiveness of the author's feelings, penetration into the inanimate phenomenon, the flow of images, manifestations of psychological character and mood are studied on specific poems and illustrated with examples. Conducting a poetic analysis of lyrical poems, the creative abilities and characteristic artistic styles of the poets were revealed. Considering that the poetic meaning of poems and individual words in the works of Abai and Mukagali lies in sincerity and harmony, the impossibility of any other use of artistic means in them is proved.In the article, the cognition, perception and evaluation of life, cognition of being, its character and feelings of a person living in contact with nature in the works of Abai and Mukagali were studied using specific examples. Comparing the lyrics of two Kazakh poets, the analysis of their poetic specificity, creative skill, artistic imagination contributes to the recognition of various traditions of Kazakh poetry, the understanding of works, the development of a model of artistic analysis.